Efficacy and Safety of Ligation Combined With Sclerotherapy for Patients With Acute Esophageal Variceal Bleeding in Cirrhosis: A Meta-Analysis - Su, Juan; Zhang, Huilin; Ren, Maifang; Xing, Yanan; Yin, Yuefei; Liu, Lihua (Frontiers in Surgery, 2021)
Objective To evaluate the efficacy and safety of EVL combined EIS for controlling AVB. Methods Online databases including Web of Science, PubMed, the Cochrane Library, Chinese National Knowledge Infrastructure(CNKI), China Biology Medicine disc (CBM), VIP and Wanfang Database were searched to identify the studies which compared the differences between EVB combined EIS and EVB, EIS from databases construction to the end of December 30, 2020. STATA 13.0 was used for meta-analysis. Results A total of 8 studies involving 595 patients(317 patients in EVL group and 278 patients in EVL+EIS group) were included. The results of meta-analysis showed that there are no statistically significant difference in efficacy of acute bleeding control(RR=0.99, 95%CI: 0.63~1.56, P=0.981), overall rebleeding(RR=0.83, 95%CI: 0.52~1.31, P=0.415), variceal eradication(RR=1.01, 95%CI: 0.82~1.23, P=0.960), overall mortality(RR=0.80, 95%CI: 0.52~1.24, P=0.314), but there is a significant difference in overall complication(RR=0.60, 95%CI: 0.41~0.87, P=0.01). Conclusion EVL is is superior to the combination of EVL and EIS in safety, although with no statistically significant differences in efficacy. Further studies on these two clinical inventions should be designed as large sample, multi-center, randomized controlled trails.